A global bibliometric and visualized analysis of bacterial biofilm eradication from 2012 to 2022 - Wang, Tao; Zhang, Rui; Chen, Zhiling; Cao, Peipei; Zhou, Qionglin; Wu, Qiang (Frontiers in Microbiology, 2023)
Background To deeply explore the dynamic trends, focal points and emerging topics of bacterial biofilm eradication field and provide novel insights for prospective research endeavors, the first global bibliometric and visualized analysis of the field was employed in this study. Methods The study meticulously curated articles and reviews concentrating on biofilm eradication from the Web of Science Core Collection (WoSCC) and identified literature published in 2012–2022 for further analysis, and the bibliometric and visualized analysis was performed to elucidate a clustering pattern in the domain with tools mainly including CiteSpace and VOSviewer. Results 15,503 authors affiliated with 2,397 institutions spanning 96 countries or regions contributed to a corpus of 3,201 articles, containing 7,005 keywords. The USA emerged as a commanding vanguard in exploring the antibiofilm strategies and displaying pioneering initiatives within this sphere. The Chinese Academy of Sciences (CAS) emerged as the most prolific source of publications. Noteworthy among authors, Pandian Shunmugiah Karutha secured the lead in article contributions as well as co-citations while Deng Le with his team is poised to become a dominant influence in the future. Despite that, the extent of collaborative engagement across different institutions and authors appeared to fall short of its potential. Frontiers in Microbiology led the discourse by publishing a substantial body of articles and standing as the most recurrently co-cited publication. The most influential research domains encompassed “bacterial biofilm formation, “photodynamic therapy” and “phage therapy.” Recent trends and forefronts concentrate on intensifying research into facilitating the shift of multiple strategies for biofilm eradication from controlled lab settings or animal studies to real-world clinical environments. Conclusion Fundamentally, this study presents a comprehensive scrutiny and reveals that the realm of bacterial biofilm eradication is undergoing rapid evolution, with even greater expansion anticipated in the times ahead. Subsequent scholars should emphasize the augmentation of collaborative efforts and focus their energies on emerging topics, thus contributing to break through current barriers in transitioning biofilm eradication strategies from the “fundamental” stage to “practical” application.